Sertraline or placebo in chronic breathlessness? Lessons from placebo research - Pattinson, K; Wanigasekera, V (European Respirator Society, 2019)
We were fascinated by the recent paper from Currow et al. [1], which described the largest randomised controlled trial of an antidepressant in the treatment of chronic refractory breathlessness. This study was important as there are few pharmacological treatments available for chronic breathlessness. In this group there is an unmet clinical need for treatments that target symptoms. The study's theoretical basis was well supported by preliminary data. However, no difference was observed between sertraline and placebo for the primary outcome measure, the improvement in breathlessness intensity.